Agile project and portfolio management: A systematic literature review - Batista, F. C.; Pereira, L. F.; Costa, R. L. da. (XI PostGraduate Conference in Management, Hospitality and Tourism - Book of abstracts, 2020)
The application of Agile Methods (AM) in project management has shown great efficiency and remarkable results. However, these methods were born to be applied at team level and not at project portfolio level, where the complexity of managing multiple agile projects and teams leads to several challenges of resource management, priorities and governance model of the project portfolio. The systematic literature review performed in this research aims to identify which practices are the most appropriate to manage the challenges associated with Agile Portfolio Management (APM) and which is the most appropriate context.